Secrets of Divine Love: A Spiritual Journey into the Heart of Islam - Ratna Roshida Ab Razak, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
The book under review teaches us how to discover our true purpose in life and our spiritual potentials. It is about a spiritual journey into the heart of Islam that brings together under the theme of Divine Love the Quran's spiritual secrets, ancient mystical poetry, and stories from the world's greatest prophets and spiritual masters to help readers reawaken their faith, overcome their doubts, and build their relationship with God The author, A. Helwa uses scientific facts, practical exercises, and guided meditations as tools and means of awareness to detect and conquer the negative inner critic that prevents us from experiencing God's all-encompassing love.